Incidence, Risk Factors For Metabolic Syndrome And Health Systems Capacity For Its Management Amongst People Living With HIV, Accra-Ghana: A Study Protocol. - Odikro, M.A.; Torpey, K.; Lartey, M.; Puplampu, P.; Painstil, E.; Kenu, E. (Plos One, 2024)
Background Metabolic syndrome (MetS) refers to the clustering of three or more metabolic disorders including high blood pressure, glucose impairment, abdominal obesity, high triglycerides, and low high-density lipoproteins. MetS is increasingly being considered an epidemic among People Living With HIV (PLWH) with reports of association between HIV infection and/or antiretroviral therapy (ART) usage and development of MetS. MetS predisposes PLWH to the development of cardiovascular, kidney diseases and diabetes, decreases the quality of life, and burdens the health system. This study aims to establish the incidence, time to development and risk factors for development of MetS and it’s components, and to assess the capacity of the health system to manage MetS and it’s components among ART naive PLWH in Accra, Ghana. Methods We will conduct a mixed methods study with quantitative and qualitative data collection. Our prospective cohort study would enroll adults of 18 years and above with none or less than three MetS components at baseline and follow them up at six months and one year. Demographic, lifestyle data, anthropometric, and laboratory data will be collected using an adapted WHO Steps Survey questionnaire. The WHO Service Availability and Readiness Questionnaire (SARA) will be adapted to collect information on capacity across the six WHO building blocks. Key informant interviews will be conducted with HIV coordinators at the national, regional, and facility levels. In-depth interviews will be conducted with PLWH from the cohort who develop MetS or MetS components during their follow-up. Data will be analysed using proportions, Kaplan Mier time to event analysis, fitting of Cox proportional hazard regression models for risk factors, and generation of themes from qualitative data. Expected outcome This study will generate data on the incidence, time to development, risk factors for MetS and MetS components development, and health systems capacity for MetS management among PLWH. Findings would inform revisions to the guidelines and policies for HIV care in Ghana, Africa, and beyond, ultimately improving MetS prevention and management among the vulnerable population of PLWH.
Research Article
Keywords: Risk Factors; Metabolic Syndrome; HIV; Accra-Ghana